Unraveling the nanomechanical properties of surface-grafted conjugated polymer brushes with ladder-like architecture. Issue 44 (26th October 2020) - Słowikowska, Monika; Wolski, Karol; Wójcik, Artur J.; Wesner, Daniel; Schönherr, Holger; Zapotoczny, Szczepan
Abstract : Surface-grafted polymer brushes with ladder-like architecture enforce extended conformation of the chains affecting their mechanical and tribological properties. Abstract : Decoration of inorganic substrates with surface-grafted and perpendicularly oriented conjugated polymers has gained substantial attention spurred by the development of new facile synthetic methodologies. We have recently shown that conjugated polymer brushes with interesting optoelectrical properties and presupposed ladder-like architecture could be obtained by a self-templating surface-initiated polymerization (ST-SIP). In this report, nanomechanical properties of ladder-like brushes composed of alkyl backbones supported by conjugated polyacetylene chains are investigated by means of AFM nanoindentation, quantitative nanomechanical mapping (QNM), and lateral force microscopy (LFM) in air and organic solvents. It is shown that conversion of deprotected linear poly(3-trimethylsilyl-2-propynyl methacrylate) (PTPM) brushes into ladder-type brushes using ST-SIP leads to pronounced changes in the structure and mechanical properties of the formed films. Ladder-type brushes possess an open (porous) structure and enhanced stiffness compared to the parent brushes. In contrast to linear brushes, the Young's modulus of ladder-like brushes is shown to be independent of solvent quality, due to the low conformational freedom of the grafted chains. The LFM measurements reveal slightly enhanced lubricating properties of linear brushes. However, the differences between linear and ladder-like brushes are much smaller than those reported for typical isotropically crosslinked films. Degrafting experiments reveal the predominantly intramolecular mechanism of ST-SIP and hence efficient generation of ladder-type conjugated polymers. The observation of structure-dependent changes of mechanical properties revealed in this study indicates new opportunities to fine-tune interface properties by exploiting stretched polymer chains in advanced architectures leading to low conformational freedom.